Entrepreneurship at the Advancement of Digitalization and Artificial Intelligence: GEM Slovenia 2024, Executive Summary - Širec, Karin; Bradač Hojnik, Barbara; Rus, Matej; Tominc, Polona (2025)
The GEM survey offers an in-depth analysis of the various social, cultural, political, and economic factors that impact the entrepreneurial landscape and activities, serving as a comprehensive framework for understanding national and entrepreneurial conditions. These factors play a crucial role in shaping individuals' entrepreneurial decisions and the success of starting and operating businesses. Survey delivers unparalleled insights into a nation's entrepreneurial characteristics, surpassing the information available from traditional statistical sources. The study also explores individuals' and societies' attitudes towards entrepreneurship, alongside the aspirations and qualifications of people at different entrepreneurial stages. By examining these aspects across countries, GEM identifies key drivers and obstacles for entrepreneurship, enabling a supportive entrepreneurial ecosystem. Current edition focuses, among others, on digitalization and artificial intelligence and their impact on entrepreneurship. The emphasis is on the challenges and opportunities brought by digitalization and AI, as well as on how companies can leverage these trends for growth and development.
Keywords: Global Entrepreneurship Monitor; entrepreneurship; early-stage entrepreneurial activity; economic development; entrepreneurship ecosystem; entrepreneurship policy; sustainable business; digitalization; artificial intelligence